1999
DOI: 10.1590/1807-1929/agriambi.v3n3p417-420
|View full text |Cite
|
Sign up to set email alerts
|

Uso Do Instrumento TDR Para Determinação Do Teor De Água Em Diferentes Camadas De Um Latossolo Roxo Distrófico

Abstract: RESUMOO presente estudo teve como objetivo verificar a validade dos dados de umidade volumétrica fornecidos pelo instrumento TDR -"Time Domain Reflectometer -Trase System", para as camadas 0 -20, 0 -40 e 0 -60 cm de um Latossolo Roxo Distrófico de textura argilosa, sob experimento de cafeicultura irrigada na Universidade Federal de Lavras. As relações entre a umidade real (determinada pelo método padrão de estufa) e a constante dielétrica Ka (característica do solo obtida pelo TDR) e entre a umidade real e a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
(5 reference statements)
3
2
0
11
Order By: Relevance
“…The fits of the cubic models indicated that more than 98.6% of the variations in volumetric water content can be explained by the variations in the dielectric constant for all depths studied. The magnitude of R² was the same found by Silva and Gervásio (1999) and by Tommaselli and Bacchi (2001) for Brazilian soils. Relationships between the volumetric water content and apparent dielectric constant of the soil, at the horizons/depths of the evaluated Yellow Argisol, according to the cubic polynomial,linear, Topp et al (1980), Ledieu et al (1986), Roth et al (1990), and Malicki et al (1996) models. once air-dried, the studied soil was uniformly deposited in the containers (PVC pipes).…”
Section: Resultssupporting
confidence: 83%
“…The fits of the cubic models indicated that more than 98.6% of the variations in volumetric water content can be explained by the variations in the dielectric constant for all depths studied. The magnitude of R² was the same found by Silva and Gervásio (1999) and by Tommaselli and Bacchi (2001) for Brazilian soils. Relationships between the volumetric water content and apparent dielectric constant of the soil, at the horizons/depths of the evaluated Yellow Argisol, according to the cubic polynomial,linear, Topp et al (1980), Ledieu et al (1986), Roth et al (1990), and Malicki et al (1996) models. once air-dried, the studied soil was uniformly deposited in the containers (PVC pipes).…”
Section: Resultssupporting
confidence: 83%
“…The model fitted to the grouped data indicates a significant linear correlation between the apparent dielectric constant and the volumetric moisture of the soil (Figure 4), demonstrating that it is possible to use the coefficient of the handmade probe to determine soil volumetric moisture (Silva & Gervásio, 1999;Tommaselli & Bacchi, 2001;VillwocK et al, 2004;Santoro et al, 2009). Figure 5 shows the correlation between the β coefficient and EC TDR for the different salinity levels was excellent (R 2 = 0.997).…”
Section: Resultsmentioning
confidence: 91%
“…Em Latossolos argilosos, em razão de algumas particularidades, como os altos teores de óxidos e hidróxidos de ferro, a calibração específica é indispensável (Villwock, 2004). Silva & Gervásio (1999) obtiveram valores subestimados do teor de água medido por sonda TDR em um Latossolo muito argiloso, ao utilizar a calibração padrão do fabricante. Evett et al (2006) propuseram que a calibração dos MCP seja separada por horizonte do solo, uma vez que a permissividade aparente é influenciada por teores de matéria orgânica e argila (Veldkamp & O'Brien, 2000;Sá et al, 2008;Kaiser et al, 2010), óxidos e hidróxidos de ferro (Prevedello et al, 2007;Kaiser et al, 2010), condutividade elétrica, temperatura (Tomaselli & Bacchi, 2001;Evett et al, 2006) e densidade do solo (Malicki et al, 1996;Huang et al, 2004); atributos que podem apresentar variação no perfil do solo.…”
Section: Introductionunclassified